World cinema on demand global film cultures in the era of online distribution - Baschiera, Stefano 1977-; Fisher, Alexander (Bloomsbury Academic, 2022)
"World Cinema on Demand brings together diverse contributions by leading film and media scholars to examine world cinema’s dialogue with the transformations that took place during 2010-2014, engaging directly with ongoing debates surrounding national cinema, transnational identity, and cultural globalization, as well as ideas about genre, fandom and cinephilia. The contributions look at individual national patterns of online distribution, engaging with archives, SVODS and torrent communities. The essays also investigate the cross-cultural presence of world cinema in non-domestic online markets (such as Europe’s, for example). As a result, the volume sheds light on geo-politically specific issues of film circulation, consumption and preservation within a range of culturally diverse filmmaking contexts, including case studies from India, Nigeria, Mexico and China. In this way, the collection maps the impact of different online formats of distribution in the understanding of World Cinema, underlining the links between distribution and media provisions as well as engaging with new forms of intermediation."
Keywords: Streaming -- Kommunikationstechnik; Film